Canal Transportation and Centering Ability of Twisted File and Reciproc: A Cone-Beam Computed Tomography Assessment - Nazari Moghaddam, Kiumars; Shahab, Shahriar; Rostami, Golriz (Iranian Endodontic Journal, 2014)
Introduction: The purpose of this in vitro study was to compare the canal transportation and centering ability of Twisted File (TF) to that of Reciproc system. Methods and Materials: Forty noncalcified roots with mature apices, minimum length of 19 mm and an apical curvature of 15-30 degrees (according to Schneider’s method), from freshly extracted mandibular and maxillary teeth, were selected for this study. Samples were randomly divided into two groups (n=20) and canal preparation with either TF or Reciproc was performed according to manufacturers’ instruction. Pre- and post-instrumentation cone-beam computed tomography (CBCT) images were captured and the extent of canal transportation and centering ability of the files were calculated, using the NNT Viewer software and Photoshop CS5, at levels of 3, 4, and 5 mm from the apex. The Mann-Whitney U test was used to analyze the statistical significance between the two groups. Results: One fracture occurred in the TF group. TF produced more transportation than Reciproc in both mesiodistal and buccolingual directions; however, the difference between the two systems were not statistically significant except for the TF group at 5-mm distance from the working length, where the difference was significant(P>0.05). Conclusion: Both file systems were able keep the original curvature of the canal and thus can be considered safe for clinical application.